PENGARUH PEMBERIAN EKSTRAK DAUN BANDOTAN (Ageratum Conyzoides) TERHADAP BERAT KARKAS DAN LEMAK ABDOMINAL AYAM BROILER (Effect of Ageratum conyzoides Leaf Extract Administration on Carcass Weight and Abdominal Fat of Broilers) - Harizqi Fatwa Lingga; Sulasmi Sulasmi; Teuku Armansyah; Siti Aisyah; Ismail Ismail; Budianto Panjaitan; Razali Razali (Universitas Syiah Kuala, 2016)
This study was aimed to determine effect of bandotan (Ageratum conyzoides) leaf extract on the carcass weight and abdominal fat of broiler. A total of 15 chicken with the age of twenty five days old were used in this study and allotted into 3 groups with 5 chickens per groups. Broiler in group P0 (as a control) were not given bandotan leaf extract,whereas broiler in group 1 (P1) and group 2 (P2) was given 3 ml and 5 ml of bandotan leaf extract, respectively. The extract was orally given once daily for 5 consecutive days. Results of analysis of variance (Anova) showed that bandotan leaf extract did not significantly (P0.05) affect carcass weight and abdominal fat of broiler. The average percentage of carcass weight in groups P0, P1, dan P2 were 73.30±3.54, 71.80±3.06, and 70.33±9.18%, respectively and the average percentage of abdominal fat in group P0, P1, dan P2 were 1.99±0.68, 2.30±0.46, amd 1.96±0.18%, respectively. Based on these results it can be concluded that bandotan leaf extract could not increase carcass weight and reduce abdominal fat of broilers.